Do corporations award CEO stock options effectively? - Yermack, David (Journal of Financial Economics, 1995)
This paper analyzes stock option awards to CEOs of 792 U.S. public corporations between 1984 and 1991. Using a Black-Scholes approach, I test whether stock options' performance incentives have significant associations with explanatory variables related to agency cost reduction. Further tests examine whether the mix of compensation between stock options and cash pay can be explained by corporate liquidity, tax status, or earnings management. Results indicate that few agency or financial contracting theories have explanatory power for patterns of CEO stock option awards.